Actors and emphasis of master’s and doctoral research on subject representation in the Brazilian science (2001-2020) - de Oliveira, Lais Pereira; Grácio, Maria Cláudia Cabrini [UNESP]; Martínez-Ávila, Daniel (FapUNIFESP (SciELO), 2022)
This work deals with subject representation from its theoretical perspective in Brazil. It aims to characterize the actors and focus of the Brazilian scientific production in subject representation in doctoral dissertations and master’s theses. Methodologically, it is a descriptive study with qualitative and quantitative approaches. It is characterized as a bibliographic research working with data from the Brazilian Digital Library of Theses and Dissertations and using bibliometric techniques for the analysis and systematization of data. The results reveal Guimarães and Fujita as the main actors in the theoretical construction of the subject representation, as they are the most prolific supervisors of dissertations and theses and also appear as the most cited authors in them. Thus, Universidade Estadual Paulista, to which these researchers are affiliated, stands out as the institution with the largest production on this topic in the context of graduate studies. The main focus of these works was the theoretical aspect of the publications and the main authors on the topic and the practical aspects of the area. It is concluded that the construction of subject representation in Brazilian dissertations and theses is significantly shaped by Guimarães and Fujita, and mainly deals with the theoretical and practical approaches to the topic.
Atores e ênfases das pesquisas de mestrado e doutorado sobre Tratamento Temático da Informação no Brasil (2001-2020)
Keywords: Bibliometric study; Information organization; Subject representation